Selenium abates reproductive dysfunction via attenuation of biometal accumulation, oxido-inflammatory stress and caspase-3 activation in male rats exposed to arsenic (2019)
Frequent exposure to arsenic is well documented to impair reproductive function in humans and animals. Biological significance of inorganic selenium and organoselenium, diphenyl selenide (DPDS), has been attributed to their pharmacological activities. However, their roles in arsenic-mediated reproductive toxicity is lacking in literature. The present study evaluated the protective effects elicited by selenium and DPDS in arsenic-induced reproductive deficits in rats. Animals were either exposed to arsenic alone in drinking water at 60 µg AsO₂Na L⁻¹ or co-treated with selenium at 0.25 mg kg⁻¹ or DPDS at 2.5 mg kg⁻¹ body weight for 45 consecutive days. Results indicated that arsenic-mediated deficits in spermatogenic indices and marker enzymes of testicular function were significantly abrogated in rats co-treated with selenium or DPDS. Additionally, selenium or DPDS co-treatment prevented arsenic-mediated elevation in oxidative stress indices and significantly suppressed arsenic-mediated inflammation evidenced by diminished myeloperoxidase activity, nitric oxide, tumor necrosis factor alpha, interleukin-1 beta levels in hypothalamus, testes and epididymis of the rats. Moreover, selenium or DPDS abrogated arsenic mediated activation of caspase-3 activity and histological lesions in the treated rats. Taken together, selenium or DPDS improved reproductive function in arsenic-exposed rats via suppression of inflammation, oxidative stress and caspase-3 activation in rats.